A critical analysis of industrial slags, their hazard potential and remediation with reference to Sustainable Development Goals (SDGs) - Pratik Godbole; Pranay Meshram; Sanjeevani Jawadand; Tushar Meshram; Kirtikumar Randive (Discover Civil Engineering, 2025)
Abstract Present study presents a comprehensive review of the industrial slags in terms of their source characteristics, chemical composition, hazard potential, and economic significance highlighting their formidable role in the framework of circular economy. Slags have been looked upon with suspicion of spreading environmental toxicity, for instance, Non-ferrous slags, particularly zinc (≥ 15,000 mg/kg) and copper (≥ 10,000 mg/kg), pose the highest environmental risks due to toxic metal contents. However, recent researches have shown that the processed slags, along with waste generated during valorisation and discarded materials, are reintegrated into industrial supply chains. Slags are transformed into construction materials like concrete and asphalt making great value addition as well as reducing the environmental toxicity. Moreover, metal recovery supports sustainable resource management and decreasing reliance on primary extraction. This study demonstrates the efficacy of modern remediation techniques in mitigating slag toxicity. It highlights the economic and environmental advantages of metal recovery, and redefine slags as valuable resources. This research aligns with SDG 3 (Good Health and Well-being), SDG 6 (Clean Water and Sanitation), and SDG 12 (Responsible Consumption and Production). By bridging the gaps between the industrial productivity and environmental concerns. This study presents a replicable framework for optimizing slag management, reducing ecological risks, and fostering long-term sustainability.